Determinants of intensive Facebook usage among utar students: The implications of uses and gratifications theory - Ho, Chao Yong (2022)
Facebook is the most popular social media platform worldwide, with more than 2.85 billion monthly active users. Although Facebook is becoming increasingly popular among university students, how each factor affects their intensive Facebook usage is still an under-researched area. To address the gaps, this study examines the determinants of intensive Facebook usage among university students in Malaysia. The researcher applies the uses and gratification theory and presents five motivations to predict intensive Facebook usage, namely information seeking, affection seeking, escape, entertainment, and social interaction. In this quantitative study, the data was collected through an online survey by randomly selecting 300 students from Universiti Tunku Abdul Rahman to complete the questionnaire. IBM-SPSS software was applied to analyze the survey data. The findings revealed that the five Facebook U&G were driving factors that motivated UTAR students to use Facebook. Descriptive analysis of the intensity of Facebook usage suggested that students are active Facebook users because they use Facebook frequently and spend a lot of time on it. The findings also demonstrated that the five motivations have a positive and significant impact on intensive Facebook usage among UTAR students. This study provides an outlook for future researchers and media practitioners to investigate the driving factors that motivate intensive Facebook usage.